Pedoman & Redaksi Jurnal Media Teknik Sipil, Volume 10, Nomor 2, Agustus 2012 - Pedoman & Redaksi (Media Teknik Sipil, 2012)
Pedoman & Redaksi Jurnal Media Teknik Sipil, Volume 10, Nomor 2, Agustus 2012